The importance of corporate brand identity in business management: An application to the UK banking sector - Isabel Buil; Sara Catalán; Eva Martínez (BRQ Business Research Quarterly, 2016)
Corporate brand identity management is a key issue for any organisation. Accordingly, its study is a research field of great interest. This paper seeks to broaden the understanding of this strategic activity and its effects. Specifically, it investigates the concept of corporate brand identity from the employees' perspective in the UK financial banking sector and analyses the link between brand identity management and employees' attitudes and behaviours. Results indicate that organisations should pay special attention to the corporate brand identity management, given its influence on employees' commitment with their organisations, as well as their brand performance and satisfaction."
Keywords: 650; Corporate brand identity; Commitment; Performance; Satisfaction; Banking